Dynamic predictive modelling of the iron and sulphur compositions in an ausmelt converter - Georgalli, Gregory Andrew (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Ing.) -- University of Stellenbosch, 2002.